2003
DOI: 10.1038/sj.leu.2403009
|View full text |Cite
|
Sign up to set email alerts
|

Risk-adapted postremission therapy in acute myeloid leukemia: results of the german multicenter AML HD93 treatment trial

Abstract: The objective of the AML HD93 treatment trial was to evaluate the outcome in young adults with acute myeloid leukemia (AML) after postremission therapy was stratified according to cytogenetically defined risk. The rationales for the study design were based (i) on previous favorable results with high-dose cytarabine in AML with t(8;21), inv/t(16q22) and in AML with normal karyotype, and ii) on encouraging results obtained in several phase II trials using autologous stem cell transplantation (SCT). Between July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 44 publications
5
72
0
5
Order By: Relevance
“…28 The cytogenetically defined risk classification of AML may also have an impact in designing a treatment trial in AML by risk-adapted postremission therapy. 29 In the present series, by using various molecular technology in addition to conventional cytogenetic analysis, we identified that 47.9% (56/ 117) of patients had the four major recurrent genetic abnormalities of AML1-ETO, CBFb-MYH11, PML-RARa and MLL rearrangements defined by the WHO classification. 15 However, approximately half of children with AML have no chromosomal or genetic abnormalities that can predict outcome, efforts have been made to improve the prognostic stratification on this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…28 The cytogenetically defined risk classification of AML may also have an impact in designing a treatment trial in AML by risk-adapted postremission therapy. 29 In the present series, by using various molecular technology in addition to conventional cytogenetic analysis, we identified that 47.9% (56/ 117) of patients had the four major recurrent genetic abnormalities of AML1-ETO, CBFb-MYH11, PML-RARa and MLL rearrangements defined by the WHO classification. 15 However, approximately half of children with AML have no chromosomal or genetic abnormalities that can predict outcome, efforts have been made to improve the prognostic stratification on this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors of relapse risk in CBFb-AML subset are still a matter of debate. Female gender, older age, and low-platelet count have been reported as predictors for inferior outcome and/or shorter disease-free survival in patients enrolled in prospective trials [1,17,18]. Furthermore, higher white blood cells (WBCs) and low-platelet counts have been identified as bad predictor factors for CR achievements [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, all of the clinical trials have been characterized by lack of compliance with the assigned treatment. 13 As shown in Table 2, only 70% of patients in four of the large studies actually received an HLAidentical sibling transplant. Moreover, less than 50% of patients available for randomization to autologous BMT or conventional chemotherapy were randomized and less than 70% of patients assigned to receive autografts actually received them.…”
Section: Limitations Of Clinical Trial Datamentioning
confidence: 99%